1992
DOI: 10.1111/j.1365-2362.1992.tb01495.x
|View full text |Cite
|
Sign up to set email alerts
|

Tumor necrosis factor alpha is associated with disease activity and the degree of anemia in patients with rheumatoid arthritis

Abstract: To elucidate the role of tumor necrosis factor alpha (TNF) in determining anemia of chronic disease (ACD) in rheumatoid arthritis (RA), 24 patients were studied for disease parameters, TNF serum levels and bone marrow for erythroid colony growth and compared with six controls. Serum TNF alpha was highest in ACD and correlated well with RA disease parameters. Both TNF and other RA disease parameters correlated inversely with degree of anemia. BFUe counts were lower in ACD, correlated positively with Hb and nega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
50
1
2

Year Published

1995
1995
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(56 citation statements)
references
References 36 publications
(20 reference statements)
3
50
1
2
Order By: Relevance
“…Opposing effects of TNF-␣ at different concentrations have been observed previously in skeletal (Alvarez et al, 2001) and cardiac muscle (Mann, 2003). The 10-20 ng/ml of TNF-␣ used in the above referenced studies exceed even the pathological levels seen in severe inflammatory diseases (Vreugdenhil et al, 1992;Nakashima et al, 1995). Effect of TNF-␣ at these levels cannot be considered physiological.…”
Section: Journal Of Cell Science 120 (4)mentioning
confidence: 74%
See 1 more Smart Citation
“…Opposing effects of TNF-␣ at different concentrations have been observed previously in skeletal (Alvarez et al, 2001) and cardiac muscle (Mann, 2003). The 10-20 ng/ml of TNF-␣ used in the above referenced studies exceed even the pathological levels seen in severe inflammatory diseases (Vreugdenhil et al, 1992;Nakashima et al, 1995). Effect of TNF-␣ at these levels cannot be considered physiological.…”
Section: Journal Of Cell Science 120 (4)mentioning
confidence: 74%
“…We have observed that the addition of 0.05 ng/ml of recombinant TNF-␣ to differentiation medium, which simulates the raised TNF-␣ level in injured muscle, stimulates myogenesis in myoblasts. However, at 0.5 or 5 ng/ml [levels seen in inflammatory diseases (Vreugdenhil et al, 1992;Nakashima et al, 1995)] TNF-␣ inhibits myogenesis (Chen et al, 2007). As a pleiotropic cytokine, TNF-␣ is known to exert divergent actions depending on concentration.…”
Section: Journal Of Cell Science 120 (4)mentioning
confidence: 99%
“…That is, the lowserum-differentiation media were supplemented with TNF-␣ each day it was replaced. This is approximately the concentration of TNF-␣ seen in different pathological conditions (Vreugdenhil et al, 1992;Chen et al, 2004). For clarity, data are expressed as a ratio of the fusion index of the stressed cell group to the unstressed cell group, termed fusion index (FI) ratio.…”
mentioning
confidence: 99%
“…Adenoviruses can sometimes cause a severe multisystem or septic shock-like disease and it was found that increased IL-6, IL-8, and TNF-a levels were associated with decreased perfusion, febrile peaks, tonic clonic seizures, and septic shock in children with adenoviral infection [6]. TNF-a has also been found to be elevated in the plasma of active rheumatoid arthritis pediatric patients [7], and the highest levels were found in correlation with anemia in rheumatoid arthritis [8].…”
mentioning
confidence: 96%